MAUDHU’I HADITH RESEARCH IN CONTEMPORARY INDONESIA: Methodology, Development, and Scholarly Contributions in the Digital Age - Saputra, Edriagus; Gustianda, Nana; Kirin, Arwansyah bin; Nasution, Azhar; Johendra, Meki (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2026)
This article aims to examine the concept, methodology, and development of maudhu’i (thematic) hadith research in the context of contemporary Islamic studies in Indonesia. Maudhu’i hadith is a relevant strategic approach in responding to the social, legal, and moral dynamics of Muslims through a comprehensive thematic understanding of the hadiths of the Prophet Muhammad ﷺ. This research employs a qualitative method with a library research approach to explore the trends, patterns, and scientific contributions of published thematic hadith studies. Data was collected through two main platforms: Dimensions.ai to trace global and national trends in relevant scientific publications, and the Science and Technology Index (SINTA) to track accredited national journals containing articles in the field of Hadith Science and Islamic Studies. Data analysis was conducted using qualitative-descriptive techniques, classified based on themes, methodologies, institutional affiliations, and the growth in the number of publications year over year. The research findings indicate that maudhu’i hadith research has experienced significant development in Indonesia, supported by the increasing number of Hadith Studies programmes and the academic productivity of lecturers and researchers at various universities. This study also found that the integration of thematic approaches with digital technology has strengthened the effectiveness of Hadith research and made it more applicable. These findings confirm that thematic Hadith research plays a crucial role in the development of modern Islamic studies and enriches the body of Islamic knowledge in the digital age. Artikel ini bertujuan untuk mengkaji konsep, metodologi, dan perkembangan riset hadis maudhu’i (tematik) dalam konteks studi Islam kontemporer di Indonesia. Hadis maudhu’i merupakan pendekatan strategis yang relevan dalam menjawab dinamika sosial, hukum, dan moral umat Islam melalui pemahaman tematik yang komprehensif terhadap hadis-hadis Nabi Muhammad. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan (library research) guna mengeksplorasi kecenderungan, pola, dan kontribusi ilmiah dari kajian hadis maudhu’i yang telah dipublikasikan. Data dikumpulkan melalui dua platform utama, yaitu Dimensions.ai untuk menelusuri tren global dan nasional publikasi ilmiah yang relevan, serta Science and Technology Index (SINTA) untuk melacak jurnal-jurnal nasional terakreditasi yang memuat artikel dalam bidang Ilmu Hadis dan Studi Islam. Teknik analisis data dilakukan secara kualitatif-deskriptif dengan klasifikasi berdasarkan tema, metodologi, afiliasi institusi, serta pertumbuhan jumlah publikasi dari tahun ke tahun. Hasil penelitian menunjukkan bahwa riset hadis maudhu’i mengalami perkembangan signifikan di Indonesia, didukung oleh meningkatnya jumlah program studi Ilmu Hadis dan produktivitas akademik para dosen serta peneliti di berbagai perguruan tinggi. Kajian ini juga menemukan bahwa integrasi antara pendekatan tematik dengan teknologi digital telah memperkuat efektivitas riset hadis dan menjadikannya lebih aplikatif. Temuan ini menegaskan bahwa riset hadis maudhu’i berperan penting dalam pengembangan studi Islam modern serta memperkaya khazanah keilmuan Islam di era digital.